Eye-recognizable and repeatable biochemical flexible sensors using low angle-dependent photonic colloidal crystal hydrogel microbeads - Tsuchiya, Mio (Sci Rep, 2019)
This paper presents eye-recognizable and repeatable biochemical flexible sensors using low angle-dependent stimuli-responsive photonic colloidal crystal hydrogel (PCCG) microbeads. Thanks to the stimuli-responsive PCCG microbeads exhibiting structural color, users can obtain sensing information without depending on the viewing angle and the mechanical deformation of the flexible sensor. Temperature-responsive PCCG microbeads and ethanol-responsive PCCG microbeads were fabricated from a pre-gel solution of N-isopropylacrylamide (NIPAM) and N-methylolacrylamide (NMAM) by using a centrifuge-based droplet shooting device (CDSD). As a proof-of-concept of thin and flexible biochemical sensors, temperature- and ethanol-sensing devices were demonstrated. By comparing the structural color of the stimuli-responsive PCCG microbeads and the color chart of the device, sensing information, including skin temperature of the human body and ethanol concentration in alcoholic beverages, was obtained successively. We expect that our device design using low angle-dependent stimuli-responsive PCCG microbeads would contribute to the development of user-friendly biochemical sensor devices for monitoring environmental and healthcare targets.